A novel immunodeficient rat model supports human lung cancer xenografts. Issue 1 (26th June 2018) - He, Di; Zhang, Junhui; Wu, Wanwan; Yi, Ning; He, Wen; Lu, Ping; Li, Bin; Yang, Nan; Wang, Di; Xue, Zhigang; Zhang, Peng; Fan, Guoping; et al.
ABSTRACT: Patient‐derived xenograft (PDX) animal models allow the exogenous growth of human tumors, offering an irreplaceable preclinical tool for oncology research. Mice are the most commonly used host for human PDX models, however their small body size limits the xenograft growth, sample collection, and drug evaluation. Therefore, we sought to develop a novel rat model that could overcome many of these limitations. We knocked out Rag1, Rag2, and Il2rg in Sprague Dawley (SD) rats by clustered regularly interspaced short palindromic repeats (CRISPR)–CRISPR‐associated protein 9 technology. The development of lymphoid organs is significantly impaired in Rag1 −1− Rag2 −/− Il2rg −/Υ (designated as SD‐RG) rats. Consequently, SD‐RG rats are severely immunodeficient with an absence of mature T, B, and NK cells in the immune system. After subcutaneous injection of tumor cell lines of different origin, such as NCI‐H460, U‐87MG, and MDA‐MB‐231, the tumors grow significantly faster and larger in SD‐RG rats than in nonobese diabetic– Cg‐Prkdc scid Il2rg tm1Wjl / SzJ mice. Most important of all, we successfully established a PDX model of lung squamous cell carcinoma in which the grafts recapitulate the histopathologic features of the primary tumor for several passages. In conclusion, the severely immunodeficient SD‐RG rats support fast growth of PDX compared with mice, thus holding great potential to serve as a new model for oncology research.—He, D., Zhang, J., Wu, W., Yi, N., He, W., Lu, P., Li, B., Yang, N., Wang, D., Xue, Z., Zhang, P., Fan, G., Zhu, X. A novel immunodeficient rat model supports human lung cancer xenografts. FASEB J. 33, 140–150 (2019). www.fasebj.org